Dynamical modeling and analysis of epidemics - Ma, Zhien, 1935-; Li, Jia, 1974- (World Scientific Publishing Co. Pte. Ltd., 2009)
"This timely book covers the basic concepts of the dynamics of epidemic disease, presenting various kinds of models as well as typical research methods and results. It introduces the latest results in the current literature, especially those obtained by highly rated Chinese scholars. A lot of attention is paid to the qualitative analysis of models, the sheer variety of models, and the frontiers of mathematical epidemiology. The process and key steps in epidemiological modeling and prediction are highlighted, using transmission models of HIV/AIDS, SARS, and tuberculosis as application examples"--Provided by publisher.